(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The publication of research reports the results of systematic studies focused on generating scientific data for the concentration level and the distribution of the radionuclide around NAPS. It is essential to estimate the natural levels of radioactivity in the soil to examine the extent up to which the population in the surrounding is exposed. The ambient gamma absorbed dose rates is measured using portable “Digital Geiger Muller Counter Nuclear Radiation Detector. The activity equivalent to Radium only, the air absorbed dose rate (AAD), the effective dose equivalent (AEDEC), the gonadal dose equivalent rate (AGDE), the external risk index, the internal risk index, the index for gamma level, cancer risk for an average lifetime, etc. were calculated and compared with the international standards. It indicates that the overall air of the study region around NAPS is found within the safety range of radiological risk and is not harmfully affecting the environment. The activity concentration of the 226Ra, 232Th and 40K in the soil samples were measured by the use of HPGe Gamma Spectrometry method. The activity of the 226Ra, 232Th and 40K in the soil varied in the range of 29.23 – 43.56 Bq/Kg, 23.41 – 37.52 Bq/Kg and 455 - 553 Bq/Kg, with the corresponding median values are found 36.29 Bq/Kg, 28.59 Bq/Kg and 514 Bq/Kg respectively. The results observed in the present study were compared with the literary values reported for other parts of India and the worldwide average values, and discussed.